1999
DOI: 10.1046/j.1365-2125.1999.00896.x
|View full text |Cite
|
Sign up to set email alerts
|

Midazolam effects on prepulse inhibition of the acoustic blink reflex

Abstract: AimsThe eye-blink response following sudden acoustic noise bursts is part of the startle reflex. The magnitude of the startle response can be attenuated by presentation of a weak stimulus before the 'startle-eliciting' stimulus ( prepulse inhibition, PPI). PPI is a stable finding in awake humans but may be altered by anaesthetic drugs. We investigated whether the application of benzodiazepines altered the magnitude of PPI in healthy male volunteers.Methods In an open-label noncontrolled investigation, the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2000
2000
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 33 publications
2
17
0
Order By: Relevance
“…The reduction of PPI could be blocked by the benzodiazepine antagonist flumazenil. It was even suggested that the assessment of PPI may be potentially useful to monitor the sedative effect of benzodiazepines (38). In agreement with this was that our subjects scored higher on the fatigue scales after the intake of diazepam compared to placebo.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…The reduction of PPI could be blocked by the benzodiazepine antagonist flumazenil. It was even suggested that the assessment of PPI may be potentially useful to monitor the sedative effect of benzodiazepines (38). In agreement with this was that our subjects scored higher on the fatigue scales after the intake of diazepam compared to placebo.…”
Section: Discussionsupporting
confidence: 71%
“…We found that diazepam decreased the amplitude in prepulse trials more after a weak prepulse than after a strong prepulse, probably because it is more easy to reduce a large than a small startle reflex. A reduction of PPI after diazepam was reported in a study with progressively increasing concentrations of midazolam (from 0.02 to 0.14 mg kg-' h-*) in humans (38). The reduction of PPI could be blocked by the benzodiazepine antagonist flumazenil.…”
Section: Discussionmentioning
confidence: 95%
“…The effect of antidepressants on startle reactivity is less clear: Phillips et al [2000] showed that amitryptyline, but not fluvoxamine or reboxetine, reduced the startle response; in contrast, Liechti et al [2001] observed an increase in startle reactivity induced by citalopram. Although inconsistent effects of benzodiazepines on startle and PPI have been reported [Abdulajawad et al, 1997;Schachinger et al, 1999]; patients treated with benzodiazepines were excluded from this study. The effect of medication on within-session habituation is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…Four FXS subjects were taking anxiolytics. Anxiolytics have been shown to have no effect (diazepam 22 ) or to reduce PPI (midazolam 23 ). The latter effect, however, was associated with sedation and severe reduction in baseline startle responding.…”
Section: Resultsmentioning
confidence: 99%